2010
DOI: 10.1103/physrevb.81.184414
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostructural properties ofHo5(Si0.8Ge0.2)

Abstract: The magnetostructural properties of Ho 5 ͑Si 0.8 Ge 0.2 ͒ 4 have been investigated both experimentally and by using first-principles theory. The compound orders ferromagnetically at 50 K, and in the temperature range of 50-100 K it exhibits a Griffiths phaselike behavior. The dc magnetization, heat capacity, and the relaxation and frequency dependence of the ac susceptibility indicate that the long-range magnetic order and a spin-glasslike state may coexist in Ho 5 ͑Si 0.8 Ge 0.2 ͒ 4 over a certain temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In the case of Ho 5 ͑Si x Ge 1−x ͒ 4 , the magnetic properties were recently reported in Ref. 30, it was also found the existence of SRMC in the PM phase confirmed by the recent work performed by Singh et al 25 The extended ͑x , T͒ phase diagram is depicted in Fig. 2͑d͒.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In the case of Ho 5 ͑Si x Ge 1−x ͒ 4 , the magnetic properties were recently reported in Ref. 30, it was also found the existence of SRMC in the PM phase confirmed by the recent work performed by Singh et al 25 The extended ͑x , T͒ phase diagram is depicted in Fig. 2͑d͒.…”
supporting
confidence: 75%
“…24͒ and also, very recently, on Ho 5 SiGe 3 . 25 Inelastic neutron-scattering studies in Tb 5 Ge 4 have been carried out to infer about the origin of such short-range correlations. [26][27][28] Previous works on Gd 5 ͑Si x Ge 1−x ͒ 4 established that the Griffiths phase arises from the onset of spin clusters at the temperature of the un-diluted magnetic phase ͑the critical temperature expected if the structure remains unchanged͒, identified as the O͑I͒.…”
mentioning
confidence: 99%
“…The temperature-dependent X-ray powder diffraction experiment confirmed that the crystal structure of Ho 5 Si 3.2 Ge 0.8 remains monoclinic below T C ¼ 50 K, in the ferromagnetic state. The magnetocaloric effect is moderate (DT ad ¼ 1.3 K for the DH ¼ 20 kOe) and exhibits a plateau-like behavior between $20 and 50 K (Singh et al, 2010b). Metastability of the low-temperature magnetization data, frequency dependence of the ac magnetic susceptibility, and strong magnetic relaxation behavior were found to coexist with the long-range ferromagnetic order in the extended temperature range below T C .…”
Section: Ho 5 Si X Ge 4àxmentioning
confidence: 90%
“…Structural, magnetic, and thermodynamic properties of the monoclinic Ho 5 Si 3.2 Ge 0.8 phase (Gd 5 Si 2 Ge 2 type) have been examined in detail by Singh et al (2010b). The temperature-dependent X-ray powder diffraction experiment confirmed that the crystal structure of Ho 5 Si 3.2 Ge 0.8 remains monoclinic below T C ¼ 50 K, in the ferromagnetic state.…”
Section: Ho 5 Si X Ge 4àxmentioning
confidence: 93%
“…While only detailed temperature-dependant neutron studies can clarify the magnetic structure of the Tb-, Dy-and Hocontaining phases, the available data suggests that a spin reorientation is likely to occur below the Curie temperatures. Spin reorientation is often observed in the rare-earth containing phases [17e19] and it can be viewed as magnetic frustration resulting from a long-range oscillatory nature of the RudermaneKitteleKasuyaeYosida (RKKY) interactions and presence of the various REeRE bonds [20]. The Curie temperatures, T C , range from 10 to 84 K and they decrease from Gd to Tm, with the exception of Tb (Table 4).…”
Section: Magnetic Properties Measurementsmentioning
confidence: 98%